A Taste of Metaphor Variation: Contrasting the Metaphorical Extensions of “stew” and “guisar” - Esbrí-Blasco, Montserrat (Respectus Philologicus, 2024)
This article examines the range of metaphors activated by the cooking term stew in English and its Spanish counterpart guisar. The data were drawn from Corpus of Contemporary American English (COCA) and Corpus del Español: Web and Dialects. The metaphors were identified by applying MIP (Pragglejaz Group, 2007) and incorporating semantic frames (Fillmore, 1982) to provide a detailed analysis of the mappings between the core frame elements involved, and the thematic roles performed by those elements. The results suggest that English and Spanish diverge considerably regarding the metaphors evoked by stew and guisar. The lemma stew activated a broader scope of metaphorical extensions than guisar. Just one shared metaphor was identified, which underscores the presence of distinct cognitive preferences within the respective languages.